OLEH-OLEH MAKANAN KHAS DAERAH ISTIMEWA YOGYAKARTA SEBAGAI DAYA TARIK WISATA GASTRONOMI - Kusumawati, Pipin; Tyas, Dyah Wahyuning; Fitriana, Fitriana; Kusumaningrum, Haritsah (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2023)
Visiting a tourist destination frequently inspired the tourist to purchase the food souvenirs for one's family or close acquaintances. They desired to bestow upon those closest to them a memento or impression of a tourist destination in addition to an expression of affection. Yogyakarta Special Region (DIY) is a popular tourist destination among both domestic and international visitors. Recognizing this opportunity, numerous small and medium-sized enterprises (SMSE) manufactured the assortment of foods intended for sale to tourists as food gifts. Many of these options, however, were